New Wave Simulations to the (3+1)-Dimensional Modified Kdv-Zakharov-Kuznetsov Equation - Baskonus, Haci Mehmet; Koc, Dilara Altan; Gulsu, Mustafa; Bulut, Hasan (Amer Inst Physics, 2017)
In this study, we apply an effective method which is improved Bernoulli sub-equation function method (IBSEFM) to the (3+1)-dimensional modified KdV-Zakharov-Kuznetsov equation. It gives some new wave simulations such as complex and exponential structures. We check up whether all structures verify the (3+1)-dimensional modified KdV-Zakharov-Kuznetsov model. Then, we plot three and two dimensional surfaces of obtained solutions by using Wolfram Mathematica 9.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE
Keywords: Complex